2014
DOI: 10.1080/13670050.2014.953776
|View full text |Cite
|
Sign up to set email alerts
|

The struggle to maintain identity in higher education among Zulu-speaking students

Abstract: The 2002 Language Policy for Higher Education (LPHE) identifies the currently dominant language of instruction -English -as being a possible barrier to many African students in accessing and successfully completing studies at higher education level. The LPHE thus requires that black African languages be developed at Higher Education Institutions for use as languages of teaching and learning, alongside English and Afrikaans. It is hoped that such a move would, among other things, enable South Africans to take p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover, the findings are consistent with earlier studies in which it emerged that students from predominantly black African universities and communities envisaged a future in which they would use their L1 in the workplace (Parkinson and Crouch, 2011). Ngcobo's (2014) study on language identity in a South African higher education institution equally notes a strong correlation between the educational background and attitudes towards the role of L1 both in education and the workplace. These findings are also echoed by Street (2003Street ( , 2011 who argues that ideology in literacy is influenced by educational context.…”
Section: It Helps Us Improve Our Englishmentioning
confidence: 98%
“…Moreover, the findings are consistent with earlier studies in which it emerged that students from predominantly black African universities and communities envisaged a future in which they would use their L1 in the workplace (Parkinson and Crouch, 2011). Ngcobo's (2014) study on language identity in a South African higher education institution equally notes a strong correlation between the educational background and attitudes towards the role of L1 both in education and the workplace. These findings are also echoed by Street (2003Street ( , 2011 who argues that ideology in literacy is influenced by educational context.…”
Section: It Helps Us Improve Our Englishmentioning
confidence: 98%
“…Although the Language Policy for Higher Education (Department of Education 2002) allows students to be educated in their mother tongue when possible. Ngcobo (2014) points out that the promotion of mother tongue in the academic domain is failing, 'due to the prestige that continues to be associated with English in the economy and society' and furthermore maintains that 'the rejection of the vernacular was apparently because of the socio-economic benefits associated with English' (Ngcobo 2014, 696). Interestingly, these problems are certainly not confined to BWC students.…”
Section: Discussionmentioning
confidence: 99%
“…Multilingualism has been widely discussed in relation to the internationalisation of Higher Education (HE) driven by globalisation [3][4][5][6][7]. According to Australian Education International [8], 31.5% of all HDRs enrolled at Australian Higher Education Institutions (HEIs) were international students in 2014, the majority of whom had multilingual capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mitchell's analysis of education policies found that multilingual students are characterised as "either academic failures [with an] English deficiency or invisible in policies and practice" [9] (p. 13). Research indicates that English-only monolingualism raises educational and ethical issues concerning students' struggles to maintain their multilingual capabilities at acceptable levels of proficiency in academic domains [6,10]. Using epigraphs composed in their original languages at the beginning of each chapter, Gordin [11] reminds us that the production of scientific knowledge has always been, and continues to be, undertaken in multiple languages.…”
Section: Introductionmentioning
confidence: 99%